(3cJGH GdJYGRis - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh GdYHGS eMeO Hf jRjO GdfMhi GdeYQha HGdeHQO OYGfG Edi JCdja gPG GdcJGH ef Jcde ai CSHGH GdehJ ef GdhYX hGdJYGRi HGH ef GdJYGRi hgh CcKQ eG Jcde ajg GdfGS s
(3BNQgG (B:s
(3abGd YKeGf Hf Mfja eG cdeJg hdcfi SeYJ QShd Gddg Udi Gddg Ydgj hSde hMGVQjf aTcG Edjg PgGH GdHUQ Je cJGH GdJYGRi hGdeQGKi hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hBdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B282s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdCOHs